KESIAPAN MADRASAH IBTIDAIYAH MUHAMMADIYAH SEBAGAI SEKOLAH SIAGA BENCANA DI KECAMATAN GONDANGREJO KARANGANYAR - Siti Azizah Susilowati; Nanda Khoirunisa (Profesi Pendidikan Dasar, 2016)
The research aims was to determine the readiness of school-related disaster preparedness school in some Muhammadiyah Islamic elementary schools in District Gondangrejo. The object of research is 5 Muhammadiyah Islamic elementary schools in the district spread Gondangrejo, Karanganyar. Collecting research data form the primary data using research instrument in the form of questionnaires with quantitative descriptive analysis. The results showed that: 1) the Muhammadiyah Islamic elementary schools located in District Gondangrejo acquire preparedness index values between 0-32 with an average index value of 16 and included in katagoti “Not Ready”, 2) overall parameters included in the category of “Low” with the index value between 3-30 with the highest parameter values in school policies and lowest parameter is the parameter emergency response plan. It was concluded that the Muhammadiyah Islamic Elementary School in District Gondangrejo Karanganyar not alert to the disaster.